Perilaku Penggunaan Pestisida Kimia Yang Berisiko Pada Kesehatan Petani Hortikultura - Ilyas Ibrahim; Sahrir Sillehu; Mohammad Dahlan Sely; Wiwi Rumaolat; Siti Rochmaeda (Universitas Muhamadiyah Manado, 2024)
Pesticides are toxic chemical compounds used to control agricultural plant pests. Intense use of pesticides and not paying attention to standards for their use can have negative effects on farmers' health. The aim of this research is to identify the behavior of using chemical pesticides that pose a risk to the health of horticultural farmers in the agricultural area of ​​West Seram Regency. Method: This type of research is descriptive quantitative research with a cross-sectional study design. The population of this study were all horticultural farmers in West Seram Regency who used chemical pesticides, and the sample taken was 650 respondents based on the inclusion criteria, namely actively spraying chemical pesticides and a minimum work period of 25 years. Data collection instruments used questionnaires and observation. Data analysis uses statistical tools to describe the activities of farmers using pesticides. The results of the research show that the dominant risky behavior in using chemical pesticides and disrupting farmers' health is the behavior of not using personal protective equipment for 602 (92.6%) respondents and the behavior of using doses that do not comply with the standard for 547 (84.2%) respondents and mixing the number of types. chemical pesticides of more than 3 types as many as 546 (84%) respondents. Meanwhile, the dominant health complaints felt by farmers were skin disorders as many as 621 respondents and tremor complaints as many as 572 respondents, followed by other health complaints. In conclusion, farmers' behavior does not follow standards for pesticide use, which poses a risk to health. Suggestion; Farmers must use chemical pesticides wisely according to specified standards and must be equipped with knowledge about how to use pesticides correctly and the negative impacts on health.